The effectiveness of ifdil perceptual light technique (iplt) as a visual intervention in reducing online game addiction - Muhammad Luthfi; Silawati Silawati; Miftahhuddin Miftahhuddin; Reizki Maharani (Indonesian Institute for Counseling, Education and Theraphy, 2026)
The rapid development of digital technology has increased online gaming among adolescents, with some experiencing addiction that affects psychological, social, and academic functioning. This phenomenon was identified among adolescents in the Mulya Tarai Gading Housing Complex, Kampar Regency. This study examined the effectiveness of the Ifdil Perceptual Light Technique (IPLT) as a visual-based intervention to reduce online gaming addiction. A quantitative pre-experimental one-group pretest–posttest design was employed. From a population of 100 adolescents, six participants with moderate to high addiction levels were selected through purposive sampling. Data were collected using a Likert-based online gaming addiction scale and analyzed through descriptive statistics, normality testing, paired-sample t-tests, and Cohen’s d effect size. Results showed a reduction in the mean addiction score from 42.33 to 26.33, with a significant difference between pretest and posttest scores (p < 0.05). The findings indicate that IPLT is an effective and innovative intervention for reducing online gaming addiction and contributes to the development of adaptive visual-based counseling approaches in the digital era.